Induced Foreign Capital and Economical Impact through China’s Pilot Free Trade Zones to Mainland (International Research in Economics and Finance, 2017)
Based on panel data between 2012 and 2016, this article compares two groups of samples, which we call experimental group and controlling group, according to whether there are FTZs located. FTZ is natured by high institutional standards, facilitate trade and investment, financial innovation and open service. We empirically examine effect of FTZs on foreign direct investment. We find obvious and positive effect of consumption pull, element agglomeration and trade-driven. Regulatory innovation fosters market vitality with less reliance on government financing. However, phenomenon of “finance deviates from the real economy” and “net capital outflow” weaken pilot FTZ’s attraction to overseas capital. More domestic capitals flow into FTZ to avoid risks caused by institutional regulation. Imported electronic business should be limited by government because it heavily squeezes out local business. Financial innovation in FTZ should better support regional industrial development.